High‐dose cytarabine (24 g/m2) in combination with idarubicin (HiDAC‐3) results in high first‐cycle response with limited gastrointestinal toxicity in adult acute myeloid leukaemia. Issue 3 (27th February 2013) - Low, M.; Lee, D.; Coutsouvelis, J.; Patil, S.; Opat, S.; Walker, P.; Schwarer, A.; Salem, H.; Avery, S.; Spencer, A.; Wei, A.
Abstract Background/Aim Although induction chemotherapy comprising high‐dose cytarabine (HiDAC) in combination with idarubicin and etoposide or 'ICE' for adult acute myeloid leukaemia (AML) produces a complete remission rate of nearly 80%, gastrointestinal toxicity is significant. Omission of etoposide may produce similar clinical outcomes with potentially less gastrointestinal toxicity. Methods Fifty‐three consecutive patients aged 15–60 with newly diagnosed AML, receiving high‐dose cytarabine induction at the Alfred Hospital, Melbourne, were retrospectively analysed. Regimens included HiDAC‐3 (idarubicin 12 mg/m2 day 1–3, cytarabine 3 gm/m2 bd day 1, 3, 5, 7) or ICE (idarubicin 9 mg/m2 day 1–3, cytarabine 3 g/m2 bd day 1, 3, 5, 7, etoposide 75 mg/m2 day 1–7). Toxicity was assessed using Common Terminology Criteria for Adverse Events version 4.03. Results Thirty‐one patients received HIDAC‐3 and 22 patients received ICE induction. HiDAC‐3 was better tolerated than ICE in terms of lower frequency of grade 3–4 nausea (0% vs 41%; P < 0.01), grade 3–4 diarrhoea (26% vs 55%; P = 0.05), lower rates of radiologically evident enterocolitis (6% vs 32%; P = 0.03) and less cumulative days of total parenteral nutrition use (1.2 vs 7.3 days; P < 0.01). Times to haematological recovery were similar between the two regimens. Thirty‐day mortality was 0% for HiDAC‐3 and 9% for ICE. Eighty‐four per cent of HiDAC‐3‐treated patients achieved complete remission after the first cycle of therapy, compared with 77% with ICE. No differences in survival were evident between the two regimens. Conclusions HiDAC‐3 is a clinically effective induction regimen for adult AML, producing a high rate of first‐cycle complete remission with less treatment‐related gastrointestinal toxicity than ICE.